2011
DOI: 10.1158/1078-0432.ccr-10-2727
|View full text |Cite
|
Sign up to set email alerts
|

FGFR Signaling Promotes the Growth of Triple-Negative and Basal-Like Breast Cancer Cell Lines Both In Vitro and In Vivo

Abstract: Purpose: The oncogenic drivers of triple-negative (TN) and basal-like breast cancers are largely unknown. Substantial evidence now links aberrant signaling by the fibroblast growth factor receptors (FGFR) to the development of multiple cancer types. Here, we examined the role of FGFR signaling in TN breast cancer.Experimental Design: We examined the sensitivity of a panel of 31 breast cancer cell lines to the selective FGFR inhibitor PD173074 and investigated the potential mechanisms underlying sensitivity.Res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(138 citation statements)
references
References 43 publications
7
127
0
3
Order By: Relevance
“…The mesenchymal stem-like subtype, in particular, describes a similar group of cancers previously described as claudin-low (24), that have lower proliferation relative to those of basal-like TNBCs, and are enriched for the expression of genes associated with a cancer stem cell-like (or tumor-initiating cell-like) phenotype (24). Multiple growth factor pathways are expressed at high levels in mesenchymal-like TNBCs, with the expression of the FGF2 ligand being an important autocrine growth factor in these cancers (37). Metaplastic breast cancers, especially those composed of spindle cells, may frequently fall in this subtype (25).…”
Section: Gene Expression Subtypes Of Tnbcmentioning
confidence: 90%
“…The mesenchymal stem-like subtype, in particular, describes a similar group of cancers previously described as claudin-low (24), that have lower proliferation relative to those of basal-like TNBCs, and are enriched for the expression of genes associated with a cancer stem cell-like (or tumor-initiating cell-like) phenotype (24). Multiple growth factor pathways are expressed at high levels in mesenchymal-like TNBCs, with the expression of the FGF2 ligand being an important autocrine growth factor in these cancers (37). Metaplastic breast cancers, especially those composed of spindle cells, may frequently fall in this subtype (25).…”
Section: Gene Expression Subtypes Of Tnbcmentioning
confidence: 90%
“…We also found that FGFR inhibitors suppressed the activation of ERK and PI3K signaling pathways. Similarly, studies on breast cancer cells showed that PD173074 selectively inhibits FGFR tyrosine kinase activity, mitogen-activated protein kinase (MAPK), and PI3K signaling pathways (41,42). FRS2 itself is also a potentially attractive target for disruption of the mitogenic and tumorigenic effects of multiple FGFs.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant loops result from increased release of FGFs by tumor or stromal cells, promoting proliferation, survival, and angiogenesis. Interestingly, several studies have associated these aberrant loops with antitumor activity of either tyrosine kinase inhibitors (TKI) or antibodies directed against FGFR ligands (54)(55)(56). However, available data emerge mainly from preclinical work on cell line models, and further clinical confirmation is required.…”
Section: Dysregulation Of Fgfr Signaling In Human Malignanciesmentioning
confidence: 99%